Dependable IoT Using Blockchain-Based Technology - Zorzo, Avelino; Nunes, Henry; Lunardi, Roben; Michelin, Regio; Kanhere, Salil (Anais do Latin-American Symposium on Dependable Computing (LADC); 2018: Anais do VIII Latin-American Symposium on Dependable Computing, 2018)
In the last few years, novel approaches for using blockchain to solve Internet of Things (IoT) security and dependability issues have been proposed. Currently, different solutions were applied to Smart Homes, Smart Cities, Smart Grids, Supply Chains, Industry, and Vehicular Networks scenarios. Despite of that, the main advantages on the adoption of different architectures, models and algorithms proposed in the state of art of blockchain in IoT scenarios are not yet clear. This paper presents some discussion about the usage of blockchain technology in IoT environments and proposes a layer model of blockchains for IoT. In addition, we present an overview of the latest research regarding network architectures, consensus algorithms, data management, and applications. Finally, this paper presents open issues and future trends about blockchain in IoT.